2016
DOI: 10.1007/s00170-016-8609-1
|View full text |Cite
|
Sign up to set email alerts
|

A review of cutting path algorithms for laser cutters

Abstract: This paper presents a review of the literature on generating cutting paths for laser cutting machines. Firstly, the cutting path problem is defined including all relevant technical side constraints which exist plentifully in laser cutting. Secondly, a former classification method is updated to include all types of cutting path problems. Thirdly, a comprehensive review of solution methods and related applications is presented. Throughout the literature review, trends in research in cutting path generation and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 79 publications
0
26
0
4
Order By: Relevance
“…A review [9] of tool-path algorithms for laser cutters identified six types of problems: continuous cutting problem, endpoint cutting problem, intermittent cutting problem, touring polygons problem, TSP and GTSP. Most were solved using heuristics and meta-heuristics (74%); a few (17%) used exact algorithms and the remainder used approximation algorithms or constraint programming techniques.…”
Section: Multicriteria Optimization Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…A review [9] of tool-path algorithms for laser cutters identified six types of problems: continuous cutting problem, endpoint cutting problem, intermittent cutting problem, touring polygons problem, TSP and GTSP. Most were solved using heuristics and meta-heuristics (74%); a few (17%) used exact algorithms and the remainder used approximation algorithms or constraint programming techniques.…”
Section: Multicriteria Optimization Approachmentioning
confidence: 99%
“…The tool-path cutting problem is directly applicable to a number of processes, including laser cutting operations, where optimal torch path generation has a considerable impact on production time. In this case, the problem consists of finding the path that minimizes the total time required to cut all the parts from a sheet while respecting the precedence constraints [9]. Consequently, several commercial computer-aided design (CAD)/computer-aided manufacturing (CAM) packages offer automatic torch path sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…In the paper [3] it was proposed the version of the problem as a generalized travelling salesman problem (GTSP) with the inclusion of contours. Work [4] has a similar problem statement, but another way of heuristic solution (Tabu search). In the paper [5] the modification of the problem for the Leather cut process is shown.…”
Section: Introductionmentioning
confidence: 99%
“…Papers [2] and [6] contain classification of routing problems for cutting tool, and their authors admit that ECP (Endpoint Cutting Problem) and ICP (Intermittent Cutting Problem) technologies allow to reduce the waste of material, shorten the lengths of cutting and air moves due to the possibility of combining the boundaries of the cut out parts. The problems of reducing material waste and maximizing combination of the detail fragment contours are solved at the stage of creating the cutting plan.…”
Section: Introductionmentioning
confidence: 99%